2018
DOI: 10.5603/gp.a2018.0101
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive changes in older women after urogynaecological surgery

Abstract: Objectives: The need for pelvic floor surgery will increase with an aging population in the future. Aim of this prospective study was to evaluate the evolution of cognitive function in elderly women after urogynaecological surgery. Material and methods: Between 2010 and 2014, 51 female patients 70 years and older who underwent urogynaecological surgery participated in this study. Geriatric and urogynaecological assessment were performed before and six weeks after surgery, including the Mini-COG test, the clock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…However, prior studies have shown that the MMSE has limited ability to detect mild cognitive impairment 25 . In a cohort of patients aged 70 years and older undergoing POP surgery, Brander et al 6 reported a significant increase in cognitive dysfunction using paper‐based Mini‐COG and clock‐drawing tests. Using a paper‐based neurocognitive test battery, Ackenbom et al 7 reported that one‐third of patients undergoing prolapse surgery had significant cognitive dysfunction 2 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior studies have shown that the MMSE has limited ability to detect mild cognitive impairment 25 . In a cohort of patients aged 70 years and older undergoing POP surgery, Brander et al 6 reported a significant increase in cognitive dysfunction using paper‐based Mini‐COG and clock‐drawing tests. Using a paper‐based neurocognitive test battery, Ackenbom et al 7 reported that one‐third of patients undergoing prolapse surgery had significant cognitive dysfunction 2 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition to the risks associated with undergoing surgery at an older age, surgery for POP, in particular, can be of long duration, further increasing the potential risk for cognitive dysfunction. 5 In a group of women with a high rate of baseline cognitive dysfunction (15.7%), Brander et al 6 reported an increased risk of cognitive dysfunction in older women undergoing prolapse and incontinence surgery. Ackenbom et al 7 also reported an increase in postoperative cognitive dysfunction at 2 weeks following urogynecological surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to OAB symptoms, hysterectomy may be associated with depression and cognitive symptoms, although studies are still conflicting. Brandner et al, 2018, showed, an overall decline in cognitive function in a vulnerable group of elderly women during the short-term postoperative period [26]. Lewicka et al concluded that women submitted to gynecological surgery were more likely to have depression.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of 71 patients aged 46–64 years undergoing elective cardiac surgery revealed that the incidence of postoperative cognitive dysfunction (POCD) could be as high as 33% ( Oyoshi et al, 2023 ). Elderly female patients undergoing non-cardiac surgery of the peripheral system, such as urogynecological surgery including incontinence surgery, vaginal suspension, vaginal hysterectomy, or laparoscopic vaginal sacral fixation, demonstrated an increased incidence of abnormal cognition at 6 weeks postoperatively ( Brandner et al, 2018 ). Total hip arthroplasty or femoral head replacement can significantly increase the incidence of neurocognitive impairment during the awakening period and while in the hospital ( Bhushan et al, 2022 ), and it is noteworthy that anesthetic drug overuse and general anesthesia are frequently avoided based on a cerebral protection standpoint because patients are often elderly, and a Meta-analysis incorporating eight randomized controlled trials (RCTs) including 3,555 patients reported that there was no significant difference in the incidence of POCD after choosing general or regional anesthesia for elderly patients undergoing such procedures, suggesting that severe peripheral injury is the main cause of cognitive impairment ( Bhushan et al, 2022 ).…”
Section: Peripheral Inflammation and Neurocognitive Impairmentmentioning
confidence: 99%